PHARMACOGNOSTIC INVESTIGATION OF GALANTHUS WORONOWII LOSINSK. AND GALANTHUS NIVALIS L. HERBAL PHARMACEUTICAL SUBSTANCES (MICROSCOPIC AND MACROSCOPIC ANALYSIS) - Bokov, Dmitry Olegovich (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Today drug produced from snowdrop species (Galanthus woronowii Losinsk. and Galanthus nivalis L.) used in Russian traditional medicine for nervous and cardiovascular systems disorders treatment.Pharmacognostic study of fresh snowdrop plants including macroscopic and microscopic (morpho-anatomical diagnostic features) evaluation for identification of herbal pharmaceutical substances (HPS). Methods: Macro- and micro-scopic evaluation was carried out according to general pharmacopeial monographs of State Pharmacopoeia of Russian Federation XIII ed., Photographs were obtained by the microscope Altami 139Tâ€ (10Ã— eyepiece and lenses: 4Ã—, 10Ã—, 40Ã—, 100Ã—) with a digital camera eyepiece UCMOS05100KPA; images were processed using Altami Studio program. Results: In a pharmacognostic study of G. nivalis and G. woronowii HPS linear dimensions were determined. Several microscopic diagnostics and anatomical signs of snowdrops were investigated: Adaxial and abaxial leaf epidermis; epidermis of corolla, peduncle; internal and external outer scale epidermis, internal and external storage scale epidermis, and sizes of cells and cellular inclusions (starch grains and calcium oxalate raphides). G. woronowii and G. nivalis HPS possess differences both in the micro and macro levels in the linear dimensions. In general, dimensions of G. nivalis organs are much smaller than G. woronowii ones, this aspect is also expressed in the cell structures linear dimensions. The complex of macro- and micro- diagnostic signs allows to identify the snowdrop species. Conclusion: The results of the investigation can be used in routine quality control and for inclusion of pharmacopeial monographs for snowdrop HPSs.